2007
DOI: 10.1111/j.1469-0691.2006.01564.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a commercial IgE ELISA in comparison with IgA and IgM ELISAs, IgG avidity assay and complement fixation for the diagnosis of acute toxoplasmosis

Abstract: A panel of sera from patients with known case histories representative of acute toxoplasmosis (primarily lymphadenopathy, n = 106), latent toxoplasmosis (asymptomatic, n = 368) and negative samples (n = 54) was used to evaluate the capacity of five serological tests to differentiate among patients with acute or latent toxoplasmosis and non-infected individuals. Positive IgA, IgE and IgM ELISA results and low IgG avidity and complement fixation test (CFT) titres of >or=256 were considered to be indicative of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
52
2
19

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 25 publications
0
52
2
19
Order By: Relevance
“…The intensity of many toxoplasmosis-associated changes, such as personality factor changes (Flegr et al, 2000) or the impairment of reaction times (Havlíček et al, 2001), are negatively correlated with the concentration of anti-Toxoplasma antibodies measured with CFT. It has been shown that CFT titres are probably a better proxy for the duration of the infection than the concentration of IgG measured with enzyme-linked immunosorbent assay (Kodym et al, 2007) but worse than-now rarely usedindirect immunofluorescence assay (Kaňková et al, 2007). Partial Tau correlations (age controlled) that are significant after the correction for multiple tests are printed in bold.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of many toxoplasmosis-associated changes, such as personality factor changes (Flegr et al, 2000) or the impairment of reaction times (Havlíček et al, 2001), are negatively correlated with the concentration of anti-Toxoplasma antibodies measured with CFT. It has been shown that CFT titres are probably a better proxy for the duration of the infection than the concentration of IgG measured with enzyme-linked immunosorbent assay (Kodym et al, 2007) but worse than-now rarely usedindirect immunofluorescence assay (Kaňková et al, 2007). Partial Tau correlations (age controlled) that are significant after the correction for multiple tests are printed in bold.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that the patients studied tend to have recurrence of ocular toxoplasmosis between the second and fourth decades, as discussed by Holland (2004) and Lynch et al (2008). A minimum follow-up time of two years was used to reduce the probability of detecting antibodies related to the acute event because serum IgM and IgA can be detected up to 18 months and nine months, respectively, following systemic toxoplasmosis (Kodym et al 2007). Patients included in this study had at least one recurrence of acute toxoplasmosis, which was indicated by a scar associated with the active satellite lesion at the time of follow-up, and all were positive for tear SIgA specific for T. gondii during the acute phase of ocular toxoplasmosis.…”
mentioning
confidence: 86%
“…It is known that anti-T. gondii IgA plasma levels rise during the acute phase of systemic infection and remain elevated for up to nine months decreasing afterwards to normal levels (Kodym et al 2007). From an ophthalmologists' perspective, it is important to understand the behavior of SIgA during active ocular toxoplasmosis infection, as well as after the symptoms have cleared.…”
mentioning
confidence: 99%
“…Most commercial tests compare their results with those of the Sabin-Feldman IgG dye test without reaching 100% correlation; moreover, the IgG dye test detects IgG earlier than other methods (9)(10)(11)(12). For Toxoplasma IgM and IgA antibodies, there is to date no reference method and their evaluation is done by comparing one assay to another (9,(12)(13)(14)(15)(16). Positivity for IgM antibodies is often considered a marker of acute infection, as they appear in the first week following infection (3).…”
mentioning
confidence: 99%
“…However, IgM antibody positivity should be interpreted with caution, as it can persist for years after infection and there are also false-positive IgM test results (3,8,17). IgA test results are used by some laboratories as an additional marker of acute infection in the diagnosis of congenital toxoplasmosis in newborns and could also be used as a marker of reactivation in immunocompromised patients (13,18,19).…”
mentioning
confidence: 99%